Integrity of clinical information in computerized order requisitions for diagnostic imaging. (5th December 2018) - Lacson, Ronilda; Laroya, Romeo; Wang, Aijia; Kapoor, Neena; Glazer, Daniel I; Shinagare, Atul; Ip, Ivan K; Malhotra, Sameer; Hentel, Keith; Khorasani, Ramin
Abstract: Objective: Assess information integrity (concordance and completeness of documented exam indications from the electronic health record [EHR] imaging order requisition, compared to EHR provider notes), and assess potential impact of indication inaccuracies on exam planning and interpretation. Methods: This retrospective study, approved by the Institutional Review Board, was conducted at a tertiary academic medical center. There were 139 MRI lumbar spine (LS-MRI) and 176 CT abdomen/pelvis orders performed 4/1/2016-5/31/2016 randomly selected and reviewed by 4 radiologists for concordance and completeness of relevant exam indications in order requisitions compared to provider notes, and potential impact of indication inaccuracies on exam planning and interpretation. Forty each LS-MRI and CT abdomen/pelvis were re-reviewed to assess kappa agreement. Results: Requisition indications were more likely to be incomplete (256/315, 81%) than discordant (133/315, 42%) compared to provider notes ( p  < 0.0001). Potential impact of discrepancy between clinical information in requisitions and provider notes was higher for radiologist's interpretation than for exam planning (135/315, 43%, vs 25/315, 8%, p  < 0.0001). Agreement among radiologists for concordance, completeness, and potential impact was moderate to strong (Kappa 0.66-0.89). Indications in EHR order requisitions are frequently incomplete or discordant compared to physician notes, potentially impacting imaging exam planning, interpretation and accurate diagnosis. Such inaccuracies could also diminish the relevance of clinical decision support alerts if based on information in order requisitions. Conclusions: Improved availability of relevant documented clinical information within EHR imaging requisition is necessary for optimal exam planning and interpretation.